2021
DOI: 10.31083/j.rcm2202046
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disease management in heart failure: focus on telemedicine and remote monitoring

Abstract: In the context of the COVID-19 pandemic, many barriers to telemedicine disappeared. Virtual visits and telemonitoring strategies became routine. Evidence is accumulating regarding the safety and efficacy of virtual visits to replace in-person visits. A structured approach to virtual encounters is recommended. Telemonitoring includes patient reported remote vital sign monitoring, information from wearable devices, cardiac implantable electronic devices and invasive remote hemodynamic monitoring. The intensity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 88 publications
0
25
0
2
Order By: Relevance
“…A big novelty of the REMOTIVATE‐HF trial lies in the method of intervention administration. First, the sessions will be conducted remotely, with a series of advantages, such as extended access to care and higher flexibility in case of a need for frequent visits with healthcare professionals (Alvarez et al, 2021; Nardo et al, 2021). We opted for videoconferencing as this approach most closely resembles classic face‐to‐face visits.…”
Section: Discussionmentioning
confidence: 99%
“…A big novelty of the REMOTIVATE‐HF trial lies in the method of intervention administration. First, the sessions will be conducted remotely, with a series of advantages, such as extended access to care and higher flexibility in case of a need for frequent visits with healthcare professionals (Alvarez et al, 2021; Nardo et al, 2021). We opted for videoconferencing as this approach most closely resembles classic face‐to‐face visits.…”
Section: Discussionmentioning
confidence: 99%
“…These formats are fully complementary. [23][24][25] In fact, different studies have demonstrated that within the comprehensive management of patients with HF, the addition of telemedicine may result in better outcomes, including the prevention of further HF events and reduction of costs, regardless frailty status of patients. [26][27][28][29][30][31] Therefore, both, telemedicine and face-to-face visits are useful tools that can be adapted to the need that the patient require at each moment.…”
Section: Dovepressmentioning
confidence: 99%
“…If not proactively addressed, these disparities may preclude equitable access to teleneurology services across diverse populations and potentially exacerbate pre-existing health care inequalities, particularly among underserved minority populations, elderly patients, and patients with low health literacy or digital literacy. 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 It is estimated that over one in four Americans lack access to requisite technologies or digital literacy to engage in telemedicine visits, raising concerns that patients who are most vulnerable and in need of enhanced health care access may be the ones who are least likely to benefit from the advent of telemedicine technologies. 90 These issues are further magnified in considering access to teleneurology in less developed countries.…”
Section: Justice and Equity In Teleneurologymentioning
confidence: 99%